2004
DOI: 10.1634/stemcells.22-1-51
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome Profile of Human Embryonic Stem Cells as Defined by SAGE

Abstract: Human embryonic stem (ES) cell lines that have the ability to self-renew and differentiate into specific cell types have been established. The molecular mechanisms for self-renewal and differentiation, however, are poorly understood. We determined the transcriptome profiles for two proprietary human ES cell lines (HES3 and HES4, ES Cell International), and compared them with murine ES cells and other human tissues. Human and mouse ES cells appear to share a number of expressed gene products although there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
327
1
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(352 citation statements)
references
References 49 publications
(85 reference statements)
18
327
1
6
Order By: Relevance
“…Since the first derivation of hESC lines in 1998, information on gene expression in hESCs and other human stem cells has been accumulated rapidly using a variety of techniques, including microarray, SAGE, EST scan, and MPSS [17][18][19][20][21]24]. A large number of genes have been identified that are expressed at high levels in undifferentiated hESCs, and "stemness" genes that define a stem cell state have been proposed [18,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first derivation of hESC lines in 1998, information on gene expression in hESCs and other human stem cells has been accumulated rapidly using a variety of techniques, including microarray, SAGE, EST scan, and MPSS [17][18][19][20][21]24]. A large number of genes have been identified that are expressed at high levels in undifferentiated hESCs, and "stemness" genes that define a stem cell state have been proposed [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…A large dataset on gene expression of undifferentiated hESCs and EBs that differentiated from them has been generated using large-scale array experiments, including MPSS, EST enumeration, and microarrays, and described by a variety of investigators [17][18][19][20][21][22][23][24]. To generate a list of genes characteristic of undifferentiated hESCs and differentiated EBs, we examined three published reports on gene expression in hESCs and EBs: (a) a list of 92 genes identified as "stemness" genes that are expressed at high levels in six hESC lines as assessed by a 16,695 70-bp oligonucleotide microarray [18], (b) a comprehensive list of genes common to undifferentiated hESCs obtained by MPSS analysis using pooled hESCs samples [17], and (c) a large list of genes that are highly expressed in differentiated EBs detected by both MPSS and EST scan [19].…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In human tissues, Lin28 expression has been detected in normal ovarian surface epithelium (Viswanathan et al, 2009) as well as in mature oocytes (Assou et al, 2009). Lin28 expression is high in human and mouse embryonic stem (ES) cells, and decreases dramatically during ES cell differentiation (Richard et al, 2004;Darr and Benvenisty, 2008). The biological importance of Lin28 is further underscored by its ability to facilitate the reprograming of human somatic cells to induced pluripotent stem cells (Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These include the fact that induced HMGA over-expression has been reported to increase cell sensitivity to killing by genotoxic agents such as UV light [4], cisplatin and bleomycin [5], doxorubicin (a topoisomerase II inhibitor) and X-ray irradiation [39]. Additionally, cells that naturally over-express HMGA proteins [4,5,[39][40][41][42] have been demonstrated to not only be deficient in NER [4,43] but also to exhibit increased sensitivity to DNA damage induced by both chemical agents, such as cisplatin or bleomycin [5,39], and UV light [4,43]. Intriguingly, it has been speculated that the deficiency in NER and increased sensitivity to UV photolesions observed in mouse ES cells that express high levels of HMGA proteins [42] are likely mechanisms to avoid the accumulation of mutated cells during embryogenesis [43].…”
Section: Discussionmentioning
confidence: 99%